Students’ Awareness in Coping with Pronunciation Problems: A Study Among the Second Semester Students of English Department FKIP at University of Mataram - Dhea Amalia; Muhammad Amin; Arafiq (Program Studi Pendidikan Bahasa Inggris, 2023)
Students’ awareness is one of the challenges in language learning, one of which is aware of strategies used and the problems in pronunciation to be able to correctly produce and pronounce the sounds in the target language. This study aims at analysing how concerned students are with pronunciation problems of English, the problems in English pronunciation, and the strategies used by students in coping with pronunciation problems. Mixed method, both quantitative and qualitative method is applied in this study. There are 20 students of English department in University of Mataram taken as sample in this study. The data reveals that, with the detail 11 items, most of the students are concerned, and 4 more items are the things that they are not concerned about. Meanwhile for the pronunciation problems, dental fricatives were the most common errors made by the students and followed by vowel sound and alveolar fricative as the second most error sounds, also pronunciation type of alveolar plosive, postalveolar fricative, retroflex plosive, affricative, and labiodental fricative were the least mispronounced. Thus students were also interviewed for pronunciation strategies, the result shows that most students used more than one strategies. This resulst is expected to give the students further information about new alternatives of strategies in coping with pronunciation problems to improve English speaking skill and enhance the theories and methods in the teaching of pronunciation.